Simultaneous All-Optical Channel Aggregation and De-Aggregation for 8QAM Signal in Elastic Optical Networking - Hong Liu; Hongxiang Wang; Yuefeng Ji (IEEE Photonics Journal, 2019)
A simultaneous all-optical channel aggregation and de-aggregation scheme is proposed for two 8QAM modulation formats by employing four-wave mixing (FWM) in highly nonlinear fiber. The scheme consisting of two FWM processes is simple without photoelectric conversion, which is promising to improve efficient use of the fiber resources in elastic optical networking. The feasibility of the scheme has been confirmed by the input–output constellations and waveforms. System performance is also studied as a function of the optical signal-to-noise ratio of the two 8QAM signals. Finally, some potential application scenarios have also been discussed based on the same setup.